COVID-19 cohort on children with cancer: delay in treatment and increased frequency of deaths - Ana Luiza Magalhães de Andrade Lima; Maria do Céu Diniz Borborema; Ana Paula Rodrigues Matos; Kaline Maria Maciel de Oliveira; Maria Júlia Gonçalves Mello; Mecneide Mendes Lins
Abstract Objectives: to describe epidemiological characteristics and deaths in children with cancer and COVID-19 at a reference hospital in Recife, Brazil. Methods: cohort involving children under the age of 19 underwent cancer treatment during April to July 2020. During the pandemic, real-time reverse transcriptase polymerase chain reaction assay (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS -CoV-2) in nasal / oropharyngeal swab were collected in symptomatic patients or before hospitalization. Those with detectable results were included in this cohort study. The outcomes were delayed on cancer treatment and death. Descriptive analysis was performed and presented in preliminary results. Results: 48 children participated in the cohort, mostly with hematological neoplasms (66.6%.),69% were male, median age was 5.5 years. The most frequent symptoms were fever (58.3%) and coughing (27.7%);72.9% required hospitalization, 20% had support in ICU and 10.5% on invasive ventilatory assistance.66.6% of the patients had their oncological treatment postponed, 16.6% died within 60 days after confirmation of SARS-CoV-2 infection. Conclusions: COVID-19 led a delay in the oncological treatment for children with cancer and a higher mortality frequency when compared to the historical series of the service. It would be important to analyze the risk factors to determine the survival impact.